Doa dan Misi - Sriwahyuni, Teresa Lina (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
Some outstanding missionaries from Methodist Church of the end of 19th century-early 20th century expressed that prayer and mission are closely intertwined. Their experiences in mission area showed that prayer is the most needed, though it does not mean that everything which sustain mission activities are unimportant. Two patrons of mission in the Catholic Church expressed similar opinion that prayer is the most important dimension in mission because prayer touches the heart of people more effectively. In his mission Jesus was intensely aware of the importance of prayer as he offered a prayer before choosing his disciples, at the beginning of his work, during his work, before his suffering and his death. Jesus had offered a prayer before his activities in mission because he was aware that he is the messenger of God. In other word Jesus was aware that his mission was God’s mission-Abba’s mission, and his identity was a messenger of God’s/Abba’s Kingdom. The awareness of Jesus identity and the close relationship with his father in prayer are the mode of our mission. Seeing the attitude of Jesus in doing mission one could conclude that prayer plays a pivotal role in mission and the goal of mission is to share the Kingdom of God the Father.